A Smart Hydroponics-Based System for Child Education - Dincer, Samet; Bitirim, Yiltan (Graz Univ Technolgoy, Inst Information Systems Computer Media-Iicm, 2019)
In this paper, a novel smart system based on hydroponics is proposed. It is aimed to help educate children by contributing to their improvement on cognitive domain, affective domain and psychomotor domain. This hydroponics-based smart education system is task oriented, does not interfere the child's daily needs such as studying and sleeping and includes instant child control. It is an interdisciplinary system which consists of Android application, Raspberry Pi, Web server, MySQL server and hydroponics system components. Improvement of children in terms of cognitive, affective and psychomotor could be contributed with this system's various features.
Keywords: Smart system; mobile application; embedded system; Web; MySQL; hydroponics system; child education; cognitive domain; affective domain; psychomotor domain